Biosynthesis of silver nanoparticles using Pomegranate juice extract and its antibacterial activity - Ibraheim, Mona Hussein; Ibrahiem, A.A.; Dalloul, T. R. (International Journal of Applied Sciences and Biotechnology, 2016)
Green synthesis of silver nanoparticles (AgNPs) from silver nitrate was carried out using aqueous Pomegranate juice extract (PJE) as a reducing agent. The formation of AgNPs was characterized by UV-visible (UV–vis) spectroscopy, transmission electron microscopy (TEM), Fourier transforms infrared spectroscopy and X-ray diffraction (XRD). Surface Plasmon resonance (SPR) of ∼420-423 nm confirmed the earlier formation of AgNPs. TEM and XRD analysis showed that the AgNPs with an average diameter of 23 nm are crystalline in nature and have face-centered cubic geometry. The antibacterial efficiency of AgNPs against Escherchia coli and Staphylococcus aureus showed high level of inhibition. Further, the zone of inhibition increased with the increase in the concentration of silver nanoparticles. These studies are quite useful as it shows the utility of green nanotechnology for the synthesis of silver nanoparticles without any toxic residuals and byproducts. The efficient antimicrobial activity of biosynthesized AgNPs proves the application potential in the area of nano-medicine. Int J Appl Sci Biotechnol, Vol 4(3): 254-258